Serum IL-10, IL-17 and IL-23 levels as "bioumoral bridges" between dyslipidemia and atopy. (November 2017) - Manti, S.; Leonardi, S.; Panasiti, I.; Arrigo, T.; Salpietro, C.; Cuppari, C.
Highlights: Cytokines profile in pediatric population affected by dyslipidemia and atopic predisposition. New insights on the complex crosstalk between dyslipidemia and atopy. IL-10, IL-17 and IL-23 as "bioumoral bridge" between dyslipidemia and atopy. Abstract: Background: Although several studies suggest a possible link between dyslipidemia and atopy, literature findings are still unclear. Objective: The aim of the study was to investigate the relationship between dyslipidemia and atopy in a pediatric population affected by dyslipidemia or dyslipidemia/atopic predisposition. Materials and methods: Children with dyslipidemia, dyslipidemia and atopy as well as healthy children were recruited. Serum total IgE, IL-10, IL-17, and IL-23 levels as well as fasting lipid values (total cholesterol, LDL, HDL and triglycerides) were performed on all enrolled children. Results: The present study evaluated 23 patients affected by dyslipidemia, 26 patients affected by atopy and dyslipidemia and, 22 healthy children. Serum total IgE levels significantly related also with serum cholesterol levels: positively with total cholesterol (p < 0.05), LDL (p < 0.05), and tryglicerides (p < 0.001), but negatively with HDL (p < 0.05). Serum levels of IL-10 were lower in children with atopy and dyslipidemia than patients with dyslipidemia (p < 0.001). Serum IL-10 levels significantly related also with serum cholesterol levels: negatively with total cholesterol (p < 0.001), LDL (p < 0.05), and triglycerides (p < 0.05), but positively with HDL (p < 0.05). Serum IL-17 and IL-23 levels showed the same trend. They were significantly higher in children with atopy and dyslipidemia than patients with dyslipidemia (p < 0.001). In particular, serum IL-17 and IL-23 values positively correlated with serum total IgE levels (p < 0.05); serum total cholesterol levels (p < 0.001); serum LDL levels (p < 0.001); serum triglycerides levels (p < 0.05). Although not statistically significant, an inverse correlation has been noted between serum IL-17, IL-23 and HDL levels. Conclusions: These findings support the notion that dyslipidemia and atopic predisposition share the same immune pathways as well as they offer new insights in the complex crosstalk between hyperlipidemia and atopy.